ANALISIS KONSEP KETAHANAN PANGAN DI INDONESIA DAN HUKUM PERTAMBAHAN HASIL YANG SEMAKIN MENURUN (STUDI KASUS KOMODITAS PADI DAN KEDELAI) - Umayatu Suiroh Suharto (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This research aims to determine of influence the rice and soyabean production in Indonesia since year 2011 until year 2015. This research using the Panel Data method. The result of this research in the partial either in simultenous analisys that fertilizer plants (FP), sum of productive land (L) and number of farmer (F) have an influence to the production of rice and soyabean (QP) in Indonesia since year 2011 until yaer 2015, showing as a BLUE model. This model also explained the Law of Diminishing Return, showing by an influence of farmer (F) to the production of rice and soyabean.